Constitutive mutations in the controlling site region of the araBAD operon of Escherichia coli B/r that decrease sensitivity to catabolite repression. - Colomé, J (1977)
Strains of Escherichia coli B/r containing a deletion of the regulatory gene araC are Ara-. Slow-growing revertants of these strains were isolated and designated aralc because they contain a second mutation in a controlling site, aral, that allows for a low level of constitutive expression of the araBAD operon (Englesbert et al., 1969). We mutagenized aralc delta C strains and selected mutants that grow faster in mineral L-arabinose medium. The new mutations, called araXc, map very close to the original aralc mutations and are in the controlling site region between araB and araC. The aralcXc delta C strains have a higher constitutive level of expression of the araBAD operon than the aralc delta C parents. The araXc mutations are cis acting and decrease the araBAD operon's sensitivity to catabolite repression. The araBAD operon is expressed equally well in ara delta C and ara C cya crp backgrounds. The repressor form of ara C protein is able to repress the constitutive synthesis due to the ara Xc allele.